THE EFFECT OF WATERMELON JUICE ON BLOOD PRESSURE IN ELDERLY WITH HYPERTENSION IN RW 014 JATIWARINGIN VILLAGE IN 2022 - Dini Sukmalara; Vivi Indah Safitri; Imelda Pujiharti; Marini Agustin (Jurnal Afiat : Kesehatan dan Anak, 2022)
The increase in Indonesia's population reaches 270.2 million people in 2020 and the age of the elderly and the elderly has also increased. The increasing age of the elderly and the elderly accompanied by the aging process and risky lifestyles can cause various health problems such as hypertension, triggering degenerative diseases that can lead to death such as stroke, heart disease, and kidney failure. This study aimed to determine the effect of watermelon juice on reducing blood pressure in the elderly with hypertension. Methods quasi-experimental design (one group pretest-posttest design). The total population is 46 respondents. The sample was determined by purposive sampling technique with as many as 28 respondents. The analysis in this study was univariate and bivariate using the Wilcoxon statistical test with a significance level of 95% (α = 0.05). Results obtained univariate results before intervention systolic 158.5 and diastolic 90, after intervention systolic 140.5 and diastolic 80. Bivariate results obtained systolic and diastolic blood pressure values ​​with p = 0.000 (p = <0.05). The conclusion is that there is an effect of watermelon juice on reducing blood pressure in the elderly with hypertension. Suggestions are expected for residents as input and knowledge of watermelon juice therapy to be one of the non-pharmacological therapies that can be done independently in lowering blood pressure so that it is not too high.